Influence of porosity on osteogenesis, bone growth and osteointegration in trabecular tantalum scaffolds fabricated by additive manufacturing - Jiao, Juyang; Hong, Qimin; Zhang, Dachen; Wang, Minqi; Tang, Haozheng; Yang, Jingzhou; Qu, Xinhua; Yue, Bing (Frontiers in Bioengineering and Biotechnology, 2023)
Porous tantalum implants are a class of materials commonly used in clinical practice to repair bone defects. However, the cumbersome and problematic preparation procedure have limited their widespread application. Additive manufacturing has revolutionized the design and process of orthopedic implants, but the pore architecture feature of porous tantalum scaffolds prepared from additive materials for optimal osseointegration are unclear, particularly the influence of porosity. We prepared trabecular bone-mimicking tantalum scaffolds with three different porosities (60%, 70% and 80%) using the laser powder bed fusing technique to examine and compare the effects of adhesion, proliferation and osteogenic differentiation capacity of rat mesenchymal stem cells on the scaffolds in vitro. The in vivo bone ingrowth and osseointegration effects of each scaffold were analyzed in a rat femoral bone defect model. three porous tantalum scaffolds were successfully prepared and characterized, and in vitro studies showed that while cell adhesion was better on the surface of the 60% porosity scaffold, proliferation and osteogenic differentiation were inferior to the latter two. In vivo studies further supported that the scaffolds with 70% and 80% porosity had better bone ingrowth than that of scaffolds with 60% porosity, among which the scaffold with 70% porosity had the best osseointegration effect. Therefore, the trabecular bone tantalum scaffold with 70% porosity has the optimal osteointegration and osteogenic performance, which has extremely far-reaching application prospects and provides a basis and reference for subsequent implant design, which we will further confirm in large animal preclinical models for better clinical use.